Current issues and trends in special education research, technology, and teacher preparation - Obiakor, Festus E.; Bakken, Jeffrey P.; Rotatori, Anthony F. (Bingley, U.K. : Emerald, 2010)
"This is the second of two themed volumes addressing current issues and trends in special education. Volume 20 covers research, technology, and teacher preparation whilst volume 19 covered identification, assessment and instruction. The field of special education constantly changes as a result of legislation, new instructional formats and current research investigations. It can be difficult for general and special educators, school counselors and psychologists, administrators and practicing clinicians to keep up with these changes and be current in all areas relating to special education. The special education literature knowledge base should reflect these changes; however, there is no current resource that effectively and comprehensively does this. The purpose of "Current Issues and Trends in Special Education" is to fill this void, providing chapters written by active researchers and practitioners in their respective areas.
ch. 1. Quantitative research in education : impact on evidence-based instruction / Frederick J. Brigham -- ch. 2. Qualitative research in education : other methods of seeking knowledge / Julia B. Stoner --ch. 3. Bilingualism and education : educating at-risk learners / Fabiola P. Ehlers-Zavala -- ch. 4. Mastering English to enhance education / Dike Okoro -- ch. 5. Using assistive technology to support the instructional process of students with disabilities / Howard P. Parette, George R. Peterson-Karlan -- ch. 6. Technology and students with disabilities : does it solve all the problems / Emily C. Bouck -- ch. 7. Multicultural education : a necessary tool for general and special education / Satasha L. Green -- ch. 8. Multicultural education : not a general and special education panacea / Festus E. Obiakor -- ch. 9. Transition planning, preparation, and implementation : collaboration and consultation at work / Kagendo Mutua, James Siders -- ch. 10. Transition : why it does not work / Michelle J. McCollin, Festus E. Obiakor -- ch. 11. Increasing professionalism through teacher preparation / Elizabeth Drame -- ch. 12. Teaching is not a profession : how general and special education teacher education have failed / Barbara J. Dray, Cathy Newman Thomas.
Keywords: Education -- Special Education -- General; Teaching of specific groups & persons with special educational needs; Teaching of students with specific learning difficulties / needs; Special education